2018
DOI: 10.3201/eid2406.180037
|View full text |Cite
|
Sign up to set email alerts
|

WidespreadTreponema pallidumInfection in Nonhuman Primates, Tanzania

Abstract: We investigated Treponema pallidum infection in 8 nonhuman primate species (289 animals) in Tanzania during 2015–2017. We used a serologic treponemal test to detect antibodies against the bacterium. Infection was further confirmed from tissue samples of skin-ulcerated animals by 3 independent PCRs (polA, tp47, and TP_0619). Our findings indicate that T. pallidum infection is geographically widespread in Tanzania and occurs in several species (olive baboons, yellow baboons, vervet monkeys, and blue monkeys). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Taking into account the isolation of the Fribourg-Blanc strain from Guinea baboons in 1966 and its recent sequencing and identification as a member of the TPE clade 12 , there are currently four African NHP species and five populations whose symptoms can be explained by TPE infections. Coupled with a growing number of clinical and serological observations 6 , 7 , 9 , 10 , these findings suggest that infection of NHPs with TPE is common throughout sub-Saharan Africa. Thus, humans are not the exclusive host for the yaws bacterium, as NHPs are infected with the same bacterial agent.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Taking into account the isolation of the Fribourg-Blanc strain from Guinea baboons in 1966 and its recent sequencing and identification as a member of the TPE clade 12 , there are currently four African NHP species and five populations whose symptoms can be explained by TPE infections. Coupled with a growing number of clinical and serological observations 6 , 7 , 9 , 10 , these findings suggest that infection of NHPs with TPE is common throughout sub-Saharan Africa. Thus, humans are not the exclusive host for the yaws bacterium, as NHPs are infected with the same bacterial agent.…”
mentioning
confidence: 71%
“…Indeed, a number of African NHPs show skin ulcerations that are suggestive of treponemal infections, and antibodies against TP have been detected in wild NHP populations 6 , 7 . Although genetic studies confirmed that monkeys and great apes are infected with TP strains 8 10 , most of these analyses only used short DNA sequences. Thus, the small number of examined polymorphic sites largely precluded assignment of these strains to a particular TP subspecies 9 , especially considering that sporadic recombination events between subspecies have been reported 11 .…”
mentioning
confidence: 99%
“…Wild primates (including chimpanzees, gorillas, baboons, macaques, sooty mangabeys, vervet and blue monkeys, and African green monkeys) have been observed with yaws‐like and syphilis‐like lesions; treponemal infection is supported in these animals by serological, bacteriological, or molecular evidence (Fribourg‐Blanc & Mollaret, ; Chuma et al, ; Harper et al, ; Klegarth et al, ; Knauf et al, , , ). Of particular interest, olive baboons at Lake Manyara National Park in Tanzania were observed with ulcerative lesions in the anogenital region, suggesting sexual transmission, although molecular analyses of four gene regions (Knauf et al, ) and subsequent whole genome sequencing (Knauf et al, ) showed that the causative agent was most closely related to T. pallidum subsp.…”
Section: Epidemiological and Genetic Researchmentioning
confidence: 99%
“…The fact that the Nichols strain of T. pallidum can infect humans, rabbits, and nonhuman primates, resulting in virtually identical clinical and pathological findings, suggests that mammalian immune systems interact with T. pallidum in similar ways and that T. pallidum can find permissive environments in a wide variety of mammalian bodies. Such information also is critical to current efforts to develop a treponemal vaccine and eradicate yaws (as noted by Chuma et al [] and Knauf et al []; see WHO []), a disease that in 2014 remained endemic in at least 13 countries (Mitja et al, ).…”
Section: Epidemiological and Genetic Researchmentioning
confidence: 99%
“…21 Finally, there is also evidence that non-human primates are also infected with Treponema pallidum subsp pertenue . 22,23 While no evidence currently exists for zoonotic transmission, the existence of a possible animal reservoir highlights the challenges that may emerge during an eradication campaign.…”
Section: Cme: Tropical Medicinementioning
confidence: 99%